The induced decomposition of t-butyl peroxide in solution. Part III. Decomposition of t-butyl peroxide in alkyl benzyl ethers; steric effects - Goh, S.H.; Huang, R.L.; Ong, S.H.; Sieh, I. (Royal Society of Chemistry, 1971)
Product and rate studies of the thermal decomposition of t-butyl peroxide in a series of alkyl benzyl ethers PhCH2·OR (R = Me, Et, Pri, But, or Ph) show little induced decomposition of the peroxide by the ether radical PhĊHOR, whereas in the case of the chloro-substituted ethers ArCH2·OR (Ar = 4-ClC 6H4 or 3,4-Cl2C6H3, R = Me, Et, Pri, But, or Ph) induced decomposition does occur to widely varying degrees, showing marked steric influence by the group R.